Методи сегментації зображень - Вискребенцева, С. О. (ХНУРЕ, 2019)
Today, the development of computer vision is actual, namely, to recognize the images and contents of photo and video information, which allows an increasing part of the tasks to be assigned to computing equipment. A distinctive feature of computer vision is: First, there is a lot of data; secondly, it is not known what is useful from the available information and what is not. Segmentation is intended to solve this problem.